Logiques paysagères « au miroir de l’eau ». L’évolution des lieux au prisme des rapports sociaux en Inde centrale - Simon Borja; Joël Cabalion; Vinod Chahande; Thierry Ramadier (Projets de Paysage)
Between 2004 and 2012, the conditions of a "forced displacement" of rural populations linked to the construction of a dam in central India were studied. New studies conducted since 2014 have analysed the consequences and explored partially submerged areas to highlight the socio-spatial approaches embodied by elements of the "new" landscape as experienced daily. This article analyses the effects of the transformations in the landscape brought about by the Gosikhurd dam and how they bring to light issues in the relocation of a social environment composed of castes.